Coming to terms with globalization: Hegemony and agency in British Columbia schools. - Topping, John F. (University of Ottawa (Canada), 1999)
Numerous authors in the fields of International Relations (IR) and International Political Economy (IPE) have pointed out the limits of contemporary theories in explaining the complexities of the globalization phenomenon. Greater attention to the construction of identity and to agency, it is proposed here, could well provide a more complete set of knowledge with which to better assess globalization. This thesis considers the place of Robert Cox's theory in understanding identity and agency in globalization. It examines the high school curriculum of Career and Personal Planning (CAPP), a course introduced in British Columbia, Canada, in September 1995. Through its messages to students, teachers and administrators, CAPP carries claims and assumptions about how individuals and communities in the contemporary world order construct who they are, as well as how they come to take action in matters that affect them.
Keywords: Education, Guidance and Counseling.